1995
DOI: 10.1037/1076-8971.1.4.732
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing victims and witnesses of crime.

Abstract: Research on the investigative process has emphasized that the completeness and accuracy of eyewitness accounts are important factors in whether or not the cases are solved. Eyewitness reports of crimes, however, are known to be incomplete, sometimes unreliable, and often at least partially incorrect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
118
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(124 citation statements)
references
References 78 publications
3
118
0
3
Order By: Relevance
“…A large body of research suggests that the use of openended (free recall) neutral questioning that allows one to report only information that one feels sure about and at a level of detail of one's own choosing, enhances memory accuracy considerably, as compared with the use of more focused questions (e.g., Fisher, 1995;Fisher, Falkner, Trevisan, & McCauley, 2000;Powell, Fisher, Wright, Brewer, & Williams, 2005;Wells et al, 2000). However, other studies have shown that rememberers often spontaneously respond to such questions by retrieving gist representations (Brainerd & Reyna, 2002;Pansky, 2010;Pansky & Koriat, 2004).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…A large body of research suggests that the use of openended (free recall) neutral questioning that allows one to report only information that one feels sure about and at a level of detail of one's own choosing, enhances memory accuracy considerably, as compared with the use of more focused questions (e.g., Fisher, 1995;Fisher, Falkner, Trevisan, & McCauley, 2000;Powell, Fisher, Wright, Brewer, & Williams, 2005;Wells et al, 2000). However, other studies have shown that rememberers often spontaneously respond to such questions by retrieving gist representations (Brainerd & Reyna, 2002;Pansky, 2010;Pansky & Koriat, 2004).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…It is not clear how law enforcement procedures can achieve these goals. Perhaps procedures can be improved so that they restrict contamination of the original memory, and perhaps techniques can be developed for getting more effective access to the original memory through more sophisticated interviewing (Fisher, 1995;Malpass, 1996;Malpass & Devine, 1981) or source monitoring techniques (Johnson, Hashtroudi, & Lindsay, 1993). As noted earlier, an overall difference in lineup choosing rate appears to be the major contrast between simultaneous-and sequential-lineup techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Accommodating this type of activation may be essential to reduce pain and emotions is also emphasized in best practice guidelines. For example, the Achieving best evidence guidance for interviewing victims and witnesses from the UK Ministry of Justice (2011a) Fisher and Geiselman also point out the importance of helping witnesses to control heightened arousal in investigative interviews, to be able to enhance the memory process and ability to communicate (Fisher, 1995;Fisher & Geiselman, 1992). Even though guidelines in the forensic literature emphasize the importance of regulating or reducing negative emotions in police interviews, there is little knowledge of exactly how this should be done and how the process may unfold.…”
Section: Accommodating Vulnerability and Contributing To The Healing mentioning
confidence: 99%
“…The training is based on PEACE, the British police training package in investigative interviewing (Clarke & Milne, 2001;Milne, Shaw, & Bull, 2007). PEACE incorporates two main approaches to investigative interviewing, namely the (enhanced) cognitive interview (Fisher, 1995;Fisher & Geiselman, 1992 and conversation management (Shepherd, 1988;Shepherd & Griffiths, 2013). The acronym PEACE represents the five phases of the interview; 1)…”
Section: Investigative Interviewingmentioning
confidence: 99%